Customer’s satisfaction towards islamic pawn shop (Ar-Rahnu) adopted by banks at Temerloh / Syafawati Mohd Tormidzi - Mohd Tormidzi, Syafawati (2011)
This paper explores about the factors that influence to the customers’ satisfaction towards Islamic pawn shop adopted by banks at Temerloh. Specifically, this project paper examines four (4) types of factor that contribute to the level of customers’ satisfaction. For this project paper, a questionnaire survey of 100 respondents is adopted. Agrobank and Bank Rakyat are the choices of an institution to make the questionnaire survey. It is because these two (2) types of bank are providing with Islamic pawn shop (Ar-Rahnu). This research is designed because we believe that the product called Ar-Rahnu are able to increase the revenue of institution if the institution can attract customers and increase the level of customer satisfaction to use this scheme as their sources of financial. The significant of the research is also want to expose to the readers and the future researchers that Islamic pawn shop (Ar-Rahnu) is not a second class business. The finding was discussing by using descriptive statistics analysis; multiple regression analysis and frequency distribution. The results indicate that all the independent variables except Shariah principle tend to influence to the customers’ satisfaction towards Islamic pawn shop (Ar-Rahnu) adopted by banks at Temerloh